An investigation into training and mentoring practices within the prison estate - Leonard, Liam James (Cases on forensic and criminological science for criminal detection and avoidance, 2024)
This chapter will investigate the basis for the teaching of integrity-based competencies to prison officers as part of their training. This training underpins the performance of prison officers in the execution of their daily workplace duties. At the heart of this study is a desire to understand and explain how a prison officer can be taught to go beyond what is the basic requirement in their tasks, in order to deliver the ‘safe and humane' service required of them in the prison system. The degree of success in achieving this form of elevated integrity within the prison can be seen to impact upon the lives of the prisoners in the officer's care, and on wider society as a whole. For instance, the challenges of dealing with concealment and detection avoidance of illicit substances can create problems for the inexperienced officer. Therefore, their training becomes important in successfully overcoming concealment of illegal materials. The chapter will also investigate mentoring as a key form of learning within prisons. While the world of prison is one which is closed to many in society, the author gained insights when he worked as an ‘embedded criminologist,' working as a lecturer on a prison training programme for five years between 2008 and 2013. This provided him with valuable criminological and penological understandings of the hidden world of the prison system, as well as the officers who work behind their walls.